Kawasaki disease in Malaysia: Biochemical profile, characterization, diagnosis and treatment - Cheah, Chooi San; Lee, Wendy Wei Li; Suhaini, Siti Aisyah; Azidin, Abdullah Harith; Khoo, Mohammad Shukri; Ismail, Noor Akmal Shareela; Ali, Adli (Frontiers in Pediatrics, 2023)
Kawasaki disease (KD) is an acute idiopathic systemic vasculitis with a self-limiting course that predominantly affects children under 5 years old, particularly in East Asian countries. Nevertheless, to date, the data on KD was limited in Malaysia. This study aimed to evaluate the epidemiology, clinical features, treatment, and outcomes of KD among the pediatric patients admitted to Hospital Canselor Tunku Muhriz (HCTM), Kuala Lumpur, Malaysia. A retrospective cohort study of 66500 pediatric patients presented at HCTM from 2004 to 2021 was conducted. 62 KD cases out of 66500 pediatric admissions were reported, with a male-to-female ratio of 1.58 to 1. Majority of KD patients (95.0%) were younger than 5 years old. Prior infection was reported in 5 KD patients (8.1%). Apart from the classical features, manifestations of various organ systems including cardiovascular (16.1%), gastrointestinal (43.5%), neurological (1.61%), musculoskeletal (1.61%) and genitourinary (17.7%) systems were observed. There was a significant association between sterile pyuria and coronary artery aneurysm (CAA) (p<0.05). Interestingly, abnormal liver parameters (p<0.05) and incomplete KD (p<0.05) were significantly related to IVIG resistance. The presence of family history, immunological disorder, and previous infection in our KD patients suggested the possible genetic, immunological, and infectious roles in the pathophysiology of KD. IVIG resistance is more likely to occur in KD patients with hepatic dysfunction or incomplete KD presentation. These findings highlighted the significant contribution of laboratory parameters to the prognosis of KD, prompting more in-depth research on the KD scoring systems and their relevance in this country.